Assessing the physical condition of the younger generation through the implementation of GTO tests - Bobkova E.N. ,; Vasilyeva Z.V. ,; Zyurin E.A.,; Vrublevskiy E.P. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to according to statistical data, we will examine the physical condition of the youth population in Russia aged between 6 and 17 years, using the results of the GTO complex tests for the year 2023. Methods and structure of the study. The following approaches were employed: sociological (questionnaires, content analysis), examination and analysis of the federal statistical data from the regions of Russia, observation, comparison, and mathematical and statistical processing of the findings. The research was conducted at the Federal State Budgetary Institution «Federal Scientific Center for Physical Culture and Sports» and the scientific and methodological center for the implementation of the All-Russian Physical Culture and Sports Complex «Ready for Labor and Defense» at Smolensk State University of Sports. As part of their scientific and methodological support for the industry, these institutions annually monitor the implementation of the All-Russian Physical Culture and Sports Complex «Ready for Labor and Defense» across the Russian Federation. Results and conclusions. The assessment of the physical condition of the Russian population aged 6 to 17 revealed the prevalence of certain tests among both male and female participants. However, the issue of incorporating less demanding tests into the TRP program warrants further investigation. This will enable us to make informed decisions regarding the removal of these tests from the testing regimen or the implementation of measures to promote these types of tests or revise their standards.